Influence of engine driven nickel titanium metallurgy and preparation kinematics on apical sensing during apex locator integrated instrumentation - Olcay Özdemir; Sena Kaşıkçı; Sena Kolunsağ Özbek; Mustafa Gündoğar (BMC Oral Health)
Abstract Background This study aimed to investigate the influence of multiple variations, such as different metallurgies available on the market in comparison with stainless steel, and simultaneously real-time reading and monitoring of apical sensing during instrumentation with various kinematic movements. Methods Three stages of experiment on two allocated groups of artificial root canals were conducted for the study as follows: metallurgy experiment with passive measurement of working lenght, with a gold standard apex locator device, correlation analysis of the apex locator device and an apex locator integrated engine-driven motor with passive measurement, and kinematics experiment with dynamic monitoring. For the metallurgy and kinematics experiments, the same preshaped artificial root canals (n = 26) and for correlation analysis of the devices unshaped root canals were used (n = 15). Stainless steel, conventional NiTi, M wire, CM gold, CM blue, TM wire, C wire, CM EDM, special NiTi heat-treated wire, and R phase file systems were selected for the metallurgy experiment. For the apex locator integrated engine-driven instrumentation, test groups were arranged according to movements and metallurgy (M wire-reciprocating/rotational, CM gold-reciprocating/rotational) and conducted on the same 26-block set. Shapiro‒Wilk, Wilcoxon, Mann‒Whitney U, and Kruskal‒Wallis tests were performed for the statistical analysis (p < 0.050). Results All tested metallurgies presented correlated measurements (p = 0.139); however, tapered instrumentation affected the working length (p < 0,001). The dynamic measurements (rotational/reciprocating) presented a statistically significant difference compared to the passively established actual working length (p < 0.001). A statistically difference was also obtained between reciprocating and rotational CM gold (p = 0.003); however, there was no difference between reciprocating and rotational M wire (p = 0.084). Conclusions Tapered instrumentation changes the initial working length. Different metallurgies have no variational impact on the determination of electronic working length. During apex locator integrated instrumentation, M wire files and rotational movement exhibit a more stable attitude; however, apical overextensions may be observed in all kinematics regardless of the metallurgies. Caution is recommended when using CM gold files with apex locator integrated engine-driven instrumentation, especially in reciprocating motion. Clinical relevance statement Maintaining the real-time working length between preparation stages is essential to preserve the apical structure. Dynamic monitoring of apical limit, regardless of motion type, as a supporter may promote treatment outcomes; however, using apex locator integrated instrumentation as a primary way for working length determination, as well as preparation, may cause an extension beyond safe limits.